Crystal structure of tris(1,10-phenanthroline-!2N,N')cobalt(II) diperchlorate, C36H24Cl2CoN6O8 - Chen Xia; Zhang Daopeng (Zeitschrift für Kristallographie - New Crystal Structures, 2014)
C36H24Cl2CoN6O8, monoclinic, P21/n (no. 14), a = 9.364(2) Å, b = 30.332(6) Å, c = 13.044(3) Å, ( = 110.422(4)°, V = 3471.9 Å3, Z = 4, Rgt(F) = 0.0723, wRref(F2) = 0.1991, T = 293 K.